Adopting universal testing for HIV in intensive care for patients admitted with severe pneumonia: results from our change in practice. (January 2017) - Sharvill, Rory; Fernandes, Arnold; Allen, Kate; Astin, Jeremy
Early identification of HIV infection is of obvious benefit to patients' health, yet many remain unaware of their diagnosis, with detrimental consequences. Current guidelines suggest patients with pneumonia are offered an HIV test. Early diagnosis of HIV infection in critically ill patients within intensive care is vital in reducing mortality and morbidity. In 2015, we established automated HIV testing for patients with pneumonia admitted to our intensive care unit. Prior to our change in practice, our HIV testing rate in patients with pneumonia was 29% within two weeks of admission. After implementation, 80% of patients with pneumonia were tested for HIV within 48 h (73% with 24 h). This intervention also facilitated an early and unexpected HIV diagnosis in one patient, which then allowed prompt tailored therapy and was a significant factor in their survival. Based on our success, we suggest other centres may benefit from employing a similar automated HIV testing system, especially in targeted patient groups such as severe pneumonia.